Islam and democracy after the Arab Spring - Esposito, John L. (Oxford University Press, 2016)
Introduction -- Islam, democracy and Turkey's secular state -- Iran: classical themes and contemporary challenges -- Pakistan: a work in progress -- Indonesia -- Senegal -- Tunisia -- Egypt -- Conclusion